2002
DOI: 10.1038/ng916
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SUFU predispose to medulloblastoma

Abstract: The sonic hedgehog (SHH) signaling pathway directs the embryonic development of diverse organisms and is disrupted in a variety of malignancies. Pathway activation is triggered by binding of hedgehog proteins to the multipass Patched-1 (PTCH) receptor, which in the absence of hedgehog suppresses the activity of the seven-pass membrane protein Smoothened (SMOH). De-repression of SMOH culminates in the activation of one or more of the GLI transcription factors that regulate the transcription of downstream target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
530
2
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 734 publications
(561 citation statements)
references
References 23 publications
18
530
2
9
Order By: Relevance
“…The phenotype of these mice has features resembling Gorlin's syndrome, the cancerpredisposing condition resulting from PATCHED1 insufficiency in humans. SUFU mutation has been found to be associated with some cases of human medulloblastoma (Taylor et al, 2002), but these cases are rare (Koch et al, 2004). These findings serve as a precedent for deregulation of GLI1 in the absence of aberrancy of HH or PATCHED.…”
Section: Ews/fli1 Deregulates Gli1mentioning
confidence: 90%
“…The phenotype of these mice has features resembling Gorlin's syndrome, the cancerpredisposing condition resulting from PATCHED1 insufficiency in humans. SUFU mutation has been found to be associated with some cases of human medulloblastoma (Taylor et al, 2002), but these cases are rare (Koch et al, 2004). These findings serve as a precedent for deregulation of GLI1 in the absence of aberrancy of HH or PATCHED.…”
Section: Ews/fli1 Deregulates Gli1mentioning
confidence: 90%
“…Importantly, heterozygous loss of Sufu, in conjunction with the loss of p53, leads to the development of medulloblastoma and rhabdomyosarcoma (Lee et al , 2007). Germline Sufu mutations have been identified in medulloblastoma (Taylor et al , 2002; Kool et al , 2014) and associated with the development of medulloblastoma in Gorlin syndrome (Pastorino et al , 2009; Kijima et al , 2012; Smith et al , 2014). Furthermore, somatic Sufu mutations have been identified in multiple other malignancies, including prostate cancer (Sheng et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These biochemical activities of Sufu are conserved in mammals (Kogerman et al, 1999;Jacob and Lum, 2007), and mammalian Sufu was also found to possess a nuclear activity in repressing Gli-mediated transcription via its interaction with SAP18 (Cheng and Bishop, 2002), a component of the Sin3-HDAC corepressor complex. Sufu mutations are present in 9% of medulloblastoma patients (Taylor et al, 2002), and mice that carry one target-inactivated Sufu allele exhibited heightened risk of developing medulloblastoma in p53 null background (Lee et al, 2007). Although Drosophila Sufu is not essential for embryonic development, mouse embryos devoid of Sufu die early because of multiple developmental anomalies including failure to close the neural tube (Cooper et al, 2005;Svard et al, 2006), a phenotype shared by inactivation of Ptch1.…”
Section: Introductionmentioning
confidence: 99%